Stability Analysis of Disc Brake Squeal Considering Temperature Effect - Abu Bakar, Abd Rahim; Abdul Hamid, Mohd Kameil; Dzakaria, Afandi; Abdul Ghani, Badri; Mohamad, Maziah (Faculty of Mechanical Engineering, 2006)
Passenger cars have become one of the main transportations for people travelling from one place to another. Indeed, vehicle quietness and passenger comfort issues are a major concern. One of vehicle components that occasionally generate unwanted vibration and unpleasant noise is the brake system. Brake squeal noise is the most troublesome and irritant one to both car passenger and the environment, and is expensive to brakes and carmakers in terms of warranty costs. Brake squeal has been studied over 20 years ago through experimental, analytical and numerical methods in an attempt to understand, to predict and to prevent squeal occurrence. In recent years, the finite element (FE) method has become the preferred method due to inadequacy of experimental methods in predicting squeal at early stage in the design process. However, the drawbacks of the FE method are over-predictions and missing unstable modes in the squeal frequency range. This paper attempts to improve the drawbacks by considering temperature effect, which is typically neglected by many previous investigators. Prediction of disc brake squeal is performed using complex eigenvalue analysis that available in ABAQUS V6.4. In doing so, a validated and detailed 3-D finite element model of a real disc brake is used. Predicted results are then compared to those obtained in the experimental results with and without the effect of temperature.